Spontaneous Bilateral Simultaneous Tubal Pregnancy - Vyas, Neetha M; Manjeera, L; Shetty, D; Rai, S (Nepal Journal of Obstetrics and Gynaecology, 2013)
Bilateral tubal pregnancy in absence of ovulation induction represents the rarest form of ectopic pregnancies. Among the variant of twin ectopic pregnancy, heterotopic or twin pregnancy in the same tube is higher compared to that of bilateral tubal pregnancy. Till date around 250 cases of simultaneous bilateral tubal pregnancy have been detected and many occur following assisted reproductive treatment. Preoperative diagnosis is uncommon. It is usually detected intraoperatively and so necessitates careful examination of both the adnexa. We report a case where in one tube showed ruptured tubal pregnancy and in the other tube, a mass was noticed which was suspected to be a hydrosalphnix or a pyosalphinx. Since patient had already consented for tubectomy, a bilateral salphingectomy was done. Histopathology showed bilateral tubal pregnancy. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 1 / Issue 15 / Jan- June, 2013 / 41-42 DOI: http://dx.doi.org/10.3126/njog.v8i1.8863